2013
DOI: 10.1177/0961203313485490
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric lupus nephritis: more options, more chances?

Abstract: Lupus nephritis (LN) is more common and severe in childhood-onset systemic lupus erythematosus (SLE) than in adults. It is one of the major causes of acute kidney injury (AKI) and chronic kidney disease (CKD) in children. Steroid therapy has been used as the first-line treatment for SLE since 1970, and has improved the survival of SLE patients from ∼ 50% to >80%. Over the years many immunosuppressive drugs, including pulse methylprednisolone, oral cyclophosphamide, pulse intravenous cyclophosphamide, mycopheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 88 publications
(148 reference statements)
1
47
1
5
Order By: Relevance
“…For instance, LN was associated with higher morbidity and mortality . About 50–80% of cSLE patients showed evidence of renal involvement, up to 90% within the first year of disease onset . Approximately 45% of our cases had hematuria at baseline, which included 60% of those who died versus less than 40% of those who had not.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For instance, LN was associated with higher morbidity and mortality . About 50–80% of cSLE patients showed evidence of renal involvement, up to 90% within the first year of disease onset . Approximately 45% of our cases had hematuria at baseline, which included 60% of those who died versus less than 40% of those who had not.…”
Section: Discussionmentioning
confidence: 77%
“…Some clinical findings such as renal, neurologic and hematologic manifestations are more common in cSLE than in aSLE . Moreover, cSLE has a more rapid onset, more aggressive course and a higher tendency to organ involvement and damage, especially renal disease . Besides these characteristics, longer living time with active disease and subsequently, more treatment‐related adverse effects have been associated with more prolonged complications in cSLE .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The major characteristic feature of paediatric-onset LN is acute inflammatory renal damage, which suggests that the use of immunosuppressants in the early stages of childhood LN may improve the prognosis of later stages. [56][57][58] Glucocorticoids in combination with CTX are currently a classic treatment for LN. 59 However, severe adverse reactions have also increased, such as amenorrhea, atypical hyperplasia of the cervix, leukocyte decline, infection and alopecia caused by CTX, and especially the obviously toxic effects of gonads.…”
Section: Lupus Nephritismentioning
confidence: 99%
“…233,244,572 The utility of CSA is limited by its need for careful monitoring of drug levels and its potential toxicities, including hypertension, renal impairment, effects on lipid profile, tremor, hirsutism, and gum hyperplasia. 232,579,580 Regarding nonrenal SLE, a recent multicenter, randomized, controlled trial by BILAG concluded that low-dose CSA was as effective as AZA as a steroid-sparing agent in patients with severe SLE with a similar rate of adverse drug effects. Similarly, a number of small trials have shown efficacy of TAC in LN.…”
Section: Cyclosporine and Tacrolimusmentioning
confidence: 99%